Association Between Preoperative Sleep Disturbance and Postoperative Delirium in Elderly: A Retrospective Cohort Study - Guo H; Li LH; Lv XH; Su FZ; Chen J; Xiao F; Shi M; Xie YB (Nature and Science of Sleep, 2024)
Hao Guo,1,* Li-Heng Li,2,* Xiao-Hong Lv,1,* Feng-Zhi Su,1,* Jie Chen,1,* Fei Xiao,1,3 Min Shi,1 Yu-Bo Xie1,3 1Department of Anesthesiology, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China; 2Department of Anesthesiology, The Guilin Municipal Hospital of Traditional Chinese Medicine, Guangxi, People’s Republic of China; 3Guangxi Key Laboratory of Enhanced Recovery after Surgery for Gastrointestinal Cancer, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Bo Xie, Department of Anesthesiology, The First Affiliated Hospital of Guangxi Medical University, No. 22 Shuangyong Road, Nanning, 530000, People’s Republic of China, Tel +86 13977121557, Email xybdoctor@163.comPurpose: Postoperative sleep disturbance, characterized by diminished postoperative sleep quality, is a risk factor for postoperative delirium (POD); however, the association between pre-existing sleep disturbance and POD remains unclear. This study aimed to evaluate the association between preoperative sleep disturbance and POD in elderly patients after non-cardiac surgery.Patients and methods: This retrospective cohort study was conducted at a single center and enrolled 489 elderly patients who underwent surgery between May 1, 2020, and March 31, 2021. Patients were divided into the sleep disorder (SD) and non-sleep disorder (NSD) groups according to the occurrence of one or more symptoms of insomnia within one month or sleep- Numerical Rating Scale (NRS)≥ 6 before surgery. The primary outcome was the incidence of POD. Propensity score matching analysis was performed between the two groups. Multiple logistic regression analysis was performed to identify the risk factors for POD.Results: In both the unmatched cohort (16.0% vs 6.7%, P=0.003) and the matched cohort (17.0% vs 6.2%, P=0.023), the incidence of POD was higher in the SD group than in the NSD group. In addition, the postoperative sleep quality and the VAS score at postoperative 24 h were significantly lower in the SD group than in the NSD group. Multivariate logistic regression analysis indicated that age (Odds Ratio, 1.13 [95% CI: 1.04– 1.23], P=0.003) and preoperative sleep disturbance (Odds Ratio, 3.03 [95% CI: 1.09– 9.52], P=0.034) were independent risk factors for the development of POD.Conclusion: The incidence of POD was higher in patients with pre-existing sleep disturbance than those without it. Whether improving sleep quality for preoperative sleep disturbance may help prevent POD remains to be determined.Keywords: sleep disturbances, postoperative delirium, postoperative sleep quality, postoperative pain, anesthesia